Correlation of motor dimensions of two generations of young athletes in Alpine skiing from 2001 to 2010 - Lešnik, B. (Facta Universitatis: Series Physical Education and Sport, 2017)
The dynamics of the variations of the motor status of two generations of young Alpine skiers over a ten-year period 2001-2010 was observed. The sample of participants included 58 young Alpine skiers who represented two U-14 generations (Gen1=2001/02; Gen2=2009/10) in the category of older boys in the official Alpine ski competition system of the Ski Association of Slovenia. The developed model of potential success comprised 17 motor variables, on the other hand, the criterion variable is represented by a sum of points scored according to the system of points of SAS. By using Pearson's correlation coefficients (r) we attempted to find the correlation between individual variables (Level 1) and success in competitions by individual year/generation. We determined that the trend of the number of statistically significant correlations between individual variables and the success criterion increased from 5 (Gen1; 4 variables of strength and 1 variable of coordination) to 12 (Gen2; 4 variables of strength, 2 variables of speed, 1 variable of endurance and 5 variables of basic and special coordination). The correlation between the selected sets of motor variables (Level 2) with success in competitions was calculated by using the method of multiple correlation coefficients (R). The number of multiple correlation coefficients of the motor variables sets increased from Gen1 to Gen2. The proven larger number of statistically significant correlations between measured motor abilities and competitive success is also a very important point of strategy and orientation of the National program of development of Slovenian Alpine skiing.